Potentials of fabricating porous ceramic bodies from kaolin for catalytic substrate applications - Obada, D.O.; Dodoo-Arhin, D.; Dauda, M.; et al. (Applied Clay Science, 2016)
In this work, the suitability of using kaolin–styrofoam, sawdust, and high-density polyethylene to produce porous ceramic bodies was experimentally investigated. The kaolin samples (raw and beneficiated) were characterized by the XRD, SEM, TGA/DSC, and FTIR methods. Batch formulations of the samples including the kaolin and pore formers were formed into green bodies and fired to 1150 °C. The porosities of sintered bodies were calculated and given the following: apparent porosity: 28.63%–67.13% for all the samples investigated. Samples with high-density polyethylene (HDPE) pore formers showed minor surface cracks after firing but exhibited the highest porosity levels while samples with styrofoam and saw dust exhibited uniform surface characteristics with pores, thermal stability, and no visible surface cracks. It can be concluded that formulations containing 80% kaolin can be used for the production of ceramics with porosities as high as 67% if the right pore formers are used.
Research Article
Keywords: Kaolin; Porosity; Physical properties; Pore formers; Green bodies